Formation of Negative J ⋅ E′ in the Outer Electron Diffusion Region During Magnetic Reconnection. Issue 2 (8th February 2022) - Xiong, Q. Y.; Huang, S. Y.; Zhou, M.; Yuan, Z. G.; Deng, X. H.; Jiang, K.; Wei, Y. Y.; Xu, S. B.; Zhang, J.; Zhang, Z. H.; Yu, L.; Lin, R. T.
Abstract: It is widely acknowledged that positive energy dissipation J ⋅ E ′ from the fields to the plasmas occurs in the electron diffusion region (EDR) during magnetic reconnection. There also exists negative J ⋅ E ′ in the outer EDR, but what causes such negative J ⋅ E ′ is still unclear. In the present study, we applied 2.5‐D particle‐in‐cell simulation to investigate what causes the negative J ⋅ E ′ in the outer EDR through generalized Ohm's law. It is found that the region of negative J ⋅ E ′ expands in space with the evolution of magnetic reconnection, and the embodiment of negative J ⋅ E ′ is dominated by the electron inertial term in the generalized Ohm's law due to the deceleration of the electrons in the outer EDR. This deceleration is caused by the opposite electric field compared with the ones in the inner EDR. And the opposite electric field is induced by the newly reconnected magnetic field lines in the outer EDR. Our results give a new perspective of energy transformation between the fields and the plasmas during magnetic reconnection. Plain Language Summary: Magnetic reconnection is a widespread important physical process that allows the rapid energy conversion of the magnetic field into the plasmas, resulting in the particle's acceleration/energization and the changing of magnetic field topology. Magnetic reconnection is a key mechanism responsible for Gamma ray bursts, solar flares, auroral substorm, fusion experiments, interstellar medium, astrophysical jets, galaxy clusters, etc. Previous studies of magnetic reconnection containing energy release mostly work on positive energy dissipation. However, there also exists a negative value, which means the energy of the particles is converted into magnetic energy, and what causes this negative energy dissipation is still unclear. In this study, we apply 2.5‐D particle‐in‐cell simulation to investigate the reason for this negative energy dissipation from the perspective of generalized Ohm's law in the outer electron diffusion region. It shows that this kind of negative value is concerned with the electron inertial term. The deceleration of the electrons in the outer electron diffusion region is the main contribution. Key Points: The negative J ⋅ E ′ in the outer electron diffusion region (EDR) expands in space with the time evolution The embodiment of negative J ⋅ E ′ is dominated by the electron inertial term due to the deceleration of the electrons in the outer EDR This deceleration is caused by the opposite electric field induced by the newly reconnected magnetic field lines in the outer EDR